Identifying effective strategies to instruct parents during parent-implemented intervention: The role of parent practice with feedback - Sone, Bailey J.; Lee, Jordan; Grauzer, Jeffrey; Kaat, Aaron; Roberts, Megan Y. (Early childhood research quarterly, 2023)
•This study includes an investigation of the strategies for parent instruction that were most effective in teaching different types of intervention techniques to parents of autistic children in parent-implemented intervention.•Parent practice with feedback (i.e., independent parent practice with immediate interventionist feedback) was the only instructional strategy associated with increased parent intervention technique use.•Clinicians use increased parent practice with feedback when teaching types of intervention strategies that most parents already use to some extent and when parents have higher intervention technique use at baseline.•These results suggest that parent instructional strategies that align with parents’ existing capacities may be most effective in improving parent learning. Parent-implemented interventions have positive effects on child and family outcomes, but the core components of these interventions that are used in research settings are rarely used in practice settings. One reason for this discrepancy may be uncertainty about the optimal instruction used to teach parents. This study includes an investigation the instructional strategies that were most effective in teaching different types of intervention strategies to parents of autistic children. Increased opportunities for “parent practice with feedback” (i.e., independent parent practice with immediate clinician feedback) was most predictive of parent strategy use regardless of the type of intervention strategy or parent baseline skills. Further analysis revealed that clinicians used the instructional strategy of parent practice with feedback more often when teaching intervention strategies that parents were already using to some degree before intervention (i.e., responsive strategies) and when parents had higher baseline intervention strategy use. These results suggest that instructional strategies targeting parents’ existing capacities may be most effective in improving parent learning, and in the future, researchers should investigate ways to modify and individualize parent instruction.